THE EFFECT OF MIMOSINE FROM SIMPLICIA OF THE LAMTORO LEAF ON THE HISTOPATOLOGICAL OF WHITE RATS’ TESTIS - Jessica Oktavia Simanjuntak, Sarli; Berata, I Ketut; Winaya, Ida Bagus Oka; Setiasih, Ni Luh Eka; Sudimartini, Luh Made; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2024)
Lamtoro leaves (Leucaena leucocephala) are often used as cattle feed. Lamtoro leaf feeding causes decrease in sperm concentration, in diameter of the seminiferous tubules, impaired spermatogenesis, cell degeneration and atrophy. This research aims to determine the histopathology of the testes of white rat given mimosine at different doses. This research uses 20 of 2 months old male Wistar strain white rat with 300-350 g body weight. This research used a completely randomized design (CRD) with 4 treatments, which is P0 (negative control), P1 (positive control) is given mimosine standard 5 mg/day/head, P2 is given lamtoro leaf simplicia 50 mg/day/head and P3 is given leaf simplicia lamtoro 150 mg/day/head. Treatment was given for 14 days orally and on the 15th day a necropsy of testicular organ was taken. Histopathological examination was carried out based on the presence of congestion and necrosis lesions in the seminiferous tubules. Data from testicular histopathological examination results were scored based on severity consisting of, 0 = no lesions; 1= mild lesion (focal); 2= moderate lesion (multifocal); 3 = severe (diffuse), then analyzed with the Kruskal-Wallis and Mann-Whitney tests. The results of the study showed that administration of mimosine from lamtoro leaf simplisia could cause congestion and necrosis compared to control and treatment. Administration of mimosine dose 5 mg/day/ head (P1) causes congestion and necrosis while administration of mimosine from lamtoro leaf simplicia dose 50 mg / head / day (P3) does not cause lesions and dose 150 mg/day/ head (P2) causes congestion in the testicles.